Prevalence of Crimean-Congo haemorrhagic fever in livestock following a confrmed human case in Lyantonde district, Uganda - Atim, Stella A.; Niebel, Marc; Vudriko, Patrick; Odongo, Steven; Balinandi, Stephen; Aber, Peace; Bameka, Ronald; Ademun, Anna R.; Masembe, Charles; Tweyongyere, Robert; Thomson, Emma C. (Parasites & Vectors, 2023)
Crimean-Congo haemorrhagic fever (CCHF) is a tick-borne viral infection, characterized by haemorrhagic fever in humans and transient asymptomatic infection in animals. It is an emerging human health threat causing sporadic outbreaks in Uganda. We conducted a detailed outbreak investigation in the animal population following the death from CCHF of a 42-year-old male cattle trader in Lyantonde district, Uganda. This was to ascertain the extent of CCHF virus (CCHFV) circulation among cattle and goats and to identify affected farms and ongoing increased environmental risk for future human infections.
Keywords: Livestock; Crimean-Congo haemorrhagic fever; Human